Neoadjuvant Treatment of Stage IIB/III Triple Negative Breast Cancer with Cyclophosphamide, Doxorubicin, and Cisplatin (CAP Regimen): A Single Arm, Single Center Phase II Study (GBECAM 2008/02) - Ferreira, Arlindo R.; Metzger-Filho, Otto; Sarmento, Roberta M. B.; Bines, José (Frontiers in Oncology, 2018)
Background: The DNA damaging platinum salts have been explored in the treatment of triple negative breast cancer (TNBC) based on pre-clinical, and, more recently, clinical evidence of specific susceptibility of TNBC to these agents. Despite the increased toxicity, treatment intensification with polichemotherapy improves response and might be of interest in patients presenting with large primaries. In this trial, we aimed at exploring the efficacy and tolerability of the addition of cisplatin to standard anthracycline-cyclophosphamide backbone in patients with stage IIB/III TNBC. Patients and methods: This is a single arm, single center, non-randomized, phase II trial of stage IIB/III TNBC. Patients received neoadjuvant chemotherapy with cisplatin (50 mg/m2) in combination with doxorubicin (50 mg/m2) and cyclophosphamide (500 mg/m2) every 21 days and for a total of 6 cycles (CAP). After surgery, adjuvant chemotherapy consisting of docetaxel (75 mg/m2) every 21 days was further provided for 4 cycles. Primary outcome was pathological complete response in the breast and axilla (pCR; ypT0ypN0). Secondary outcomes were safety, disease-free survival (DFS) and overall survival (OS). Results: Eight (19.5%) out of 41 patients reached a pCR and 35 (85.4%) had a clinical complete or partial response. After a median follow-up of 47.4 months (interquartile range [IQR] 30.9 – 61.9), the proportion of patients free of recurrence or death at 3 years was of 51.8% (95% CI 34.6 – 66.5%), while the proportion of patients alive at 3 years was of 55.5% (95% CI 37.8% – 70.1%). Patients with a pCR rate or family history of breast and/or ovarian cancer (FHBOC) showed a numerical but statistically non-significant trend for improved DFS and OS. The majority of patients received 6 cycles of CAP (82.9%). The 3 most common grade ≥ 3 adverse events were nausea (16.3%), vomiting (14.0%), and neutropenia (9.3%). Febrile neutropenia occurred in 3 patients (7.0%). Conclusion: Cisplatin in association with doxorubicin and cyclophosphamide was associated with a pCR rate of 19.5% in a cohort of patients with predominantly stage III tumors. The tolerability profile of this combination poses clinical challenges to its general use in clinical practice.